Managing cultural diversity in small and medium-sized organizations : a guideline for practitioners - Kühlmann, Torsten M. (Springer Gabler, 2017)
Torsten M. Kühlmann and Ramona Heinz developed this guideline in reference to a European project designed to analyze the overall situation of skilled immigrants. They show that the management of a workforce which is comprised of people from diverse cultural backgrounds is a challenge for small and medium-sized companies. In particular, the challenge is not only to find but also to integrate and retain immigrant workers and to use their potential to a full extent. This guideline has been developed in order to meet these challenges. It has a special focus on small to medium-sized organizations and sets out to give an introduction to the topic of "managing cultural diversity" and "integrating highly skilled immigrants." Contents Why Tackle Cultural Diversity? What Does Cultural Diversity Management Involve? How to Hire and Relocate Employees from Abroad How to Integrate Immigrant Employees How to Create a Positive Diversity Climate How to Evaluate Cultural Diversity Management Target Groups Researchers and students in the fields of human resource management and international management Top management, HR management, and executives in small and medium-sized organizations The Authors Torsten M. Kühlmann is full professor of business administration in the Department of Law, Economics and Business Administration, University of Bayreuth, Germany. Ramona Heinz is a research assistant at the Bayreuth Research Institute for Small and Medium Sized Organizations e.V. at the University of Bayreuth.
Keywords: Diversity in the workplace -- Management.; Personnel management.; International business enterprises.; elektronické knihy; electronic books